A mechanistic basis for the mechanical regulation of skeletal development - SHEA, CLAIRE ANN (Trinity College Dublin. School of Natural Sciences. Discipline of Zoology, 2018)
Movement is essential to embryonic skeletal development. In humans, Foetal Akinesia Deformation Syndrome results when inhibited movement causes joint contractures and weakened bones susceptible to fracture. Differentiation of skeletal tissues from mesenchymal progenitors requires precise localisation and timing of molecular and mechanical signals. Using mouse and chick models, the host lab previously showed that mechanical forces influence gene regulation and tissue patterning during skeletal development; however, there remain gaps in our understanding of the relationship between mechanical signals and skeletal development. The work presented here elucidates molecular mechanisms that underpin the influence of mechanical signals, by examining the role of Wnt and BMP signalling pathways, identifying Hippo signalling and primary cilia as potential mechanotransducers, and characterising molecular and mechanical aspects of in vitro chondrogenic pattern formation. Collectively, these data will inform avenues for exploration of the mechanoregulation of skeletal development.
APPROVED
Keywords: skeletal development, mechanoregulation, mechanosensitive, embryonic skeletogenesis, movement, chondrogenesis, osteogenesis, tissue differentiation